Analysis of playing activity of footballers 19-21-years-old age in the leading commands of Europe. - Nikolaenko V.V; Balan В.A (Kharkov National Pedagogical University, 2012)
Competition activity of footballers is considered 19-21-years-old age in the professional commands of Europe. For research it was served as information normatively-legal documents of Federations of football of leading European championships (request letters and protocols of matches). In research it was necessary to be attached to the construction of the statistical groupings, that allowed to analyse in a dynamics playing activity of footballers on the stage of training to higher achievements. Influence of the competition loadings is appraised on the organism of sportsmen. Participating of sportsmen of this age is set in compositions of professional commands - leaders of rating of UEFA. It is set that the basic failing in preparation of the Ukrainian young footballers is surplus pursuit after a result and accent on physical preparation. It gives advantage above other commands which work above the technique of game (Holland, Germany, Spain) in youth football. However, when players from youth football pass to the grown man, results sharply fall and felt substantial blanks in individual technical preparedness.